Nationwide usage of ethambutol and incidence and screening practices of optic neuropathy - Kim, Jiyeong; Kwon, Hyeon Yoon; Ahn, Seong Joon (Frontiers in Pharmacology, 2024)
Introduction Ethambutol, a key anti-tuberculosis medication, is associated with optic neuropathy, which can lead to significant vision impairment. This population-based cohort study investigated the nationwide usage of ethambutol and the incidence and screening of optic neuropathy among ethambutol users. Methods The cohort included 206,157 individuals from the Health Insurance Review and Assessment database in South Korea who initiated ethambutol therapy between 1 January 2015, and 31 December 2021. Among them, 117,309 individuals without prior ophthalmic diseases were analyzed to investigate practice patterns. The timing of the baseline examinations (an ophthalmic examination immediately preceding [within 1 month] ethambutol initiation or the first ophthalmic assessment conducted after the initiation) and subsequent monitoring and modalities used were assessed. Results The cumulative incidences of the optic neuropathy categories, overall optic neuropathy, optic neuropathy/optic neuritis, and optic atrophy, were analyzed. The annual number of ethambutol users declined over time between 2015 and 2021. The cumulative incidences of overall optic neuropathy, optic neuropathy/optic neuritis, and optic atrophy were 2.8%, 2.0%, and 0.7%, respectively. Optical coherence tomography usage for ophthalmic examinations remarkably increased from 23.9% in 2015 to 85.5% in 2021, while visual field examinations were frequently (69.6%) employed for functional assessment at the time of diagnosis. Baseline screening within 6 months of initiating ethambutol therapy was performed in 12.0%–13.1% of ethambutol initiators annually over the study period. The percentage of ethambutol initiators receiving subsequent monitoring within 6 months following baseline screening declined over time, from 13.1% in 2015 to 7.9% in 2021. Discussion The diminishing trend in monitoring emphasizes the need for improved pharmacovigilance to reduce the risk of optic atrophy and blindness through early detection.